Zoning policy changes and the urban fringe land market - Thorson, James A (Real Estate Economics, 1994)
This paper examines the effect of a zoning change on the land market in McHenry County, Illinois. One question addressed is whether zoning `'follows the market.” It is found that, for agricultural land, zoning does tend to follow the market. In addition, the effect of land prices on land use is examined. The results here, however, are mixed. In the initial years after the zoning change, a high relative price of residential land increases the probability that a parcel will be zoned residential. However, several years later, a high relative price of residential land decreases the probability that a parcel is zoned residential. This result suggests that it may take some time for a zoning change to have a significant impact on the local land market.
Keywords: dept.eco